2015
DOI: 10.1590/bjpt-rbf.2014.0113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy (808 nm) on skeletal muscle after endurance exercise training in rats

Abstract: | Background: Low-level laser therapy (LLLT) has been demonstrated to be effective in optimizing skeletal muscle performance in animal experiments and in clinical trials. However, little is known about the effects of LLLT on muscle recovery after endurance training. Objective: This study evaluates the effects of low-level laser therapy (LLLT) applied after an endurance training protocol on biochemical markers and morphology of skeletal muscle in rats. Method: Wistar rats were divided into control group (CG), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
0
6
0
1
Order By: Relevance
“…5). LLLT has been demonstrating efficiency not only improving and accelerating the skeletal muscle regeneration [1,15,17] but also providing positive influence on physical performance and muscle recovery [19,20,37,38]. In this sense, studies have been designed to evaluate the effects of combined therapies (LLLT and exercise practice) applied post muscleinduced injuries in skeletal muscle regenerative process [22,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5). LLLT has been demonstrating efficiency not only improving and accelerating the skeletal muscle regeneration [1,15,17] but also providing positive influence on physical performance and muscle recovery [19,20,37,38]. In this sense, studies have been designed to evaluate the effects of combined therapies (LLLT and exercise practice) applied post muscleinduced injuries in skeletal muscle regenerative process [22,39].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, studies have been designed to evaluate the effects of combined therapies (LLLT and exercise practice) applied post muscleinduced injuries in skeletal muscle regenerative process [22,39]. Assis et al [19,39] demonstrated that LLLT and aerobic exercise association applied post a muscle-induced atrophy model significantly reduced muscle RING-finger protein-1 and Atrogin-1 mRNA levels, preventing muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLLT promotes angiogenesis and has anti-inflammatory properties, 26 , 27 , 28 while PRP contains Platelet-derived growth factor (PDGF), Transforming growth factor (TGF-β1), and Vascular endothelial growth factor (VEGF), responsible for attracting cells to the injury site and promoting tissue regeneration. 29 , 30 These factors probably reduced the damage in cells adjacent to the injury site, resulting in a lower incidence of fibers affected by the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Az eredmények azt mutatták, hogy a hő sérülés utáni azonnali alkalmazása felgyorsította a sérült hely degenerációs folyamatát, megkönnyítette a makrofágok vándorlását, az SC-k proliferációját és differenciálódását, valamint elősegítette az izomszövet regenerációját. Az alacsony intenzitású lézerterápiát (LLLT) szintén terápiás lehetőségként tartják számon az izmok javulásának és helyreállításának stimulálására patkányokon végzett állóképességi edzések eredményeinek alapján [ASSIS et al, 2015]. Az LLLT kombinálható vérlemezkékben gazdag vérplazma adásával, ami jobb eredményeket hozott az izmok regenerációjának elősegítésében sérülések után, mint az LLLT önmagában.…”
Section: Egyéb Fejlődő Technikákunclassified